Implementación de la contabilidad comercial en autoservicio Panda de la ciudad de Loja, periodo 01 al 30 de noviembre del 2015 - Montesinos González, Andrea Lizzeth (2017)
This thesis is justified because, “IMPLEMENTACIÓN DE LA CONTABILIDAD COMERCIAL EN AUTOSERVICIO PANDA DE LA CIUDAD DE LOJA, PERIODO 01 AL 30 DE NOVIEMBRE DEL 2015”,it was run in order to have a real appreciation of the financial situation of the business, so we can raise the necessary y solutions for the existing problems. To comply with the general objective: implement a system of accounting in self-service bunch of Loja's city, which will allow to know the real situation of the company during the period 01 to 30 November 2015; be compiled documentation source to set the State of the company's initial situation; developed the initial inventory of all goods, values and obligations that has the commercial; designed documents, receipts and accounting records that support transactions made during the accounting period; were drawn up the financial statements showing the real economic, financial situation of the accounting period; were drawn up the financial statements showing the real economic, financial situation of the company; Goods account is controlled by the system of permanent account According to the results, the business has a good income and the owner was advised to continue taking the accounting basis to be implemented for real control of her sales and if necessary perform a re-categorization of the fee the, in order to avoid future fines.